A Study on the Transformative Public Library Usage of the Second Semester Students of STKIP Muhammadiyah Enrekang - Ita Sarmita Samad; Ismail Ismail (Universitas Muhammadiyah Enrekang, 2019)
This study was aimed at knowing the extent to which the use of the transformative public library of the second semester students of STKIP Muhammadiyah Enrekang. The subjects of the study were the second semester students of STKIP Muhammadiyah Enrekang in primary school teacher education department. The data was collected through interview. The result shows that the students use the transformative public library in three purposes. The first is as a media to do the assignment from the campus. The second is to read interesting books. The third is to participate in a book fair. Yet, there are some students who never use the facilities given by the public library since they never go there.